SAFANA (Sharia Fashion Navigator): Muslim Fashion Marketplace as a Catalyst of the Indonesian Economy through Penta Helix Method - Abdullah Haidar; Putri Oktavia Rusadi (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Reviewing the number of Muslim population in Indonesia which ranks first in the world and the current trend of halal lifestyle has become a paradigm for the Muslim community. In fact, halal lifestyle is one of the sub-sectors of the creative economy, where the fashion industry contributes to the growth of Indonesia's second-ranked Gross Domestic Product (GDP). Based on Focus Economy Outlook 2020 data, the creative economy contributed IDR 1,100 trillion to Indonesia's Gross Domestic Product (GDP) throughout 2020. The availability of halal lifestyle products has the potential to accelerate the growth of Muslim fashion by utilizing the potential of MSMEs in the textile sector such as convection, manufacturers fabrics, tailors, and designers through room discussion projects to produce products that are able to compete competitively in national and international markets. Based on this potential, digital innovation and creativity are needed to accelerate the growth of the creative economy. Therefore, SAFANA was designed and initiated as a marketplace platform in Indonesia to collect domestically produced Muslim fashion products to meet consumer needs for Muslim fashion products and become a catalyst for creative economic growth. The purpose of this research is to offer a marketplace-based platform that functions as a Muslim fashion navigator to accelerate the Indonesian economy through the utilization of the potential of local MSMEs, designers, communities related to Muslim fashion and various Muslim fashion brands that have become markets in the national and international arena. The use of the pentahelix method is a reference for the development of the SAFANA application to create synergies from several parties, namely ABCGM which includes A (Academic), B (Business), C (Community), G (Government) and M (Media). The opportunity from SAFANA is that the government through the Ministry of Industry is expanding the Muslim fashion export market. The methodology of this paper is a qualitative method using secondary data. The data collection technique in this study is to use a critical literature review. The data analysis technique used consisted of collection, reduction, presentation, conclusion drawing and verification. It is hoped that the presence of SAFANA will be able to increase the competitiveness of Indonesian Muslim fashion products in the national and international arena as a catalyst for the Indonesian economy.